A Pilot Study on Smart Campus: Modeling Pedestrian Behavior at An-Najah National University, New Campus - Feras Mohammad Elsaid; Watheq Ayman Sayeh (My University, 2015)
Having‎a‎look‎into‎the‎todays‎world‎of‎knowledge‎and‎business; information technology and its applications in many fields are of a great and increasing importance. The transportation field‎is,‎by‎default,‎not‎an‎exception.‎This‎is‎mainly‎due‎to‎the‎worlds‎increasing‎trend‎ towards expansion and mobility requirements as well as economic improvement, which need massive use of transportation. As for Palestine, much has to be done with this field. People here lack the knowledge connected to this field and so do no pressure on the government and the elected municipal officials to make plans for the implementation of this kind of intelligent transportation systems whatsoever. This study collected smart data and manual data in a parallel way. It found some profound problems in the study area which was in front of An-Najah National University New Campus, one of which was the effect of pedestrians on the‎vehicles‎mobility‎that‎outturned‎a‎ level of service of E, which is low compared to the vehicular volumes and width of travel way .Then the study tried‎to‎conclude‎about‎peoples‎behavior‎through‎such data in terms of speed and volume. It also reviewed some proposed solutions of the problem of multimodal mobility in front of An-Najah National University New Campus, such as a study done by senior students in their graduation project that aimed mainly to enhance mobility and safety. The study also tried to create interaction equations between multiple traffic parameters, which in most of them showed an adverse effect of pedestrians crossing the street on the vehicular mobility. It highly recommends working on the same subject in the future, but on different titles.

Having‎a‎look‎into‎the‎todays‎world‎of‎knowledge‎and‎business; information technology and its applications in many fields are of a great and increasing importance. The transportation field‎is,‎by‎default,‎not‎an‎exception.‎This‎is‎mainly‎due‎to‎the‎worlds‎increasing‎trend‎ towards expansion and mobility requirements as well as economic improvement, which need massive use of transportation. As for Palestine, much has to be done with this field. People here lack the knowledge connected to this field and so do no pressure on the government and the elected municipal officials to make plans for the implementation of this kind of intelligent transportation systems whatsoever. This study collected smart data and manual data in a parallel way. It found some profound problems in the study area which was in front of An-Najah National University New Campus, one of which was the effect of pedestrians on the‎vehicles‎mobility‎that‎outturned‎a‎ level of service of E, which is low compared to the vehicular volumes and width of travel way .Then the study tried‎to‎conclude‎about‎peoples‎behavior‎through‎such data in terms of speed and volume. It also reviewed some proposed solutions of the problem of multimodal mobility in front of An-Najah National University New Campus, such as a study done by senior students in their graduation project that aimed mainly to enhance mobility and safety. The study also tried to create interaction equations between multiple traffic parameters, which in most of them showed an adverse effect of pedestrians crossing the street on the vehicular mobility. It highly recommends working on the same subject in the future, but on different titles.
A Pilot Study on Smart Campus: Modeling Pedestrian Behavior at An-Najah National University, New Campus